Analisis Performa Kecepatan Pemrosesan Big Data Dengan Menggunakan Micro Batching Dalam Tahap Load Pada ETL Untuk Event-Data - Pasuatmadi, Putu Audi; Mahendra, Ida Bagus Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Speed performance in Big Data Processing is one of the key aspect of presenting a real-time data for a real-time analysis in various use cases. One of such data is an Event-Data or an Activity Data that is often used for making analysis and business decisions in real-time. This research focuses on analyzing the speed performance of Big Data Processing in the Load stage of Extract, Transform, Load using Micro-Batching . The speed performance is evaluated using Load-Testing with K6 and the configuration of 10 VUs and 10000 data. The Load-Testing results of the speed performance shows that implementing Micro-Batching results in 63.63% faster in performing all the request, 59.03% faster in HTTP Request Duration, and 62% faster in HTTP Request Waiting duration.